Commentary responses and conscious awareness in humans: The implications for awareness in non-human animals - Weiskrantz, L (2001)
There are several examples from human neuropsychology of the intact preservation of processes and capacities in the absence of conscious awareness by the patients. These include loss of visual awareness (blindsight), episodic memory (amnesic syndrome), attention (unilateral neglect) and language (aphasia). The implication of these and other clinical phenomena is that descriptions of ongoing behaviour are necessary but quite insufficient for making inferences about conscious awareness, because even quite 'high level' behaviour can be run off in the absence of awareness. A commentary, or independent off-line response, is a prerequisite for determining whether the subject is consciously aware. Whether or not the commentary allows an inference about awareness in animals rests ultimately on an argument from analogy, just as is the case when we make judgements about fellow humans. But when parallel disjunctions between on-line behaviour and off-line classifications are found for both human and infrahuman subjects, as is demonstrable for blindsight and amnesia, not only do they bolster inferences about common neural mechanisms, but they strengthen inferences for analogous processing and hence for conscious experience.